In Name Only? An Exploration of the Operationalization of Empowerment Outcomes in Transformative Participatory Evaluations - Tucker, Joanne (Université d'Ottawa / University of Ottawa, 2016)
This thesis presents an exploration of the operationalization of empowerment outcomes in research on transformative participatory evaluations, focusing on the context of international development evaluation. Covering a 15 year period from 1999 and 2014, through the examination of the empirical research literature, the study explores: 1) how empowerment outcomes are measured, 2) the extent to which these outcomes demonstrate empowerment principles, and 3) which factors and conditions appear to enable or detract from the attainment of these outcomes. I found that the current state of the empirical research on transformative participatory evaluation to be largely comprised of reflective case narratives that rely solely on scarcely documented qualitative methods. In general, transformative outcomes do tend to mirror empowerment principles such as ownership, inclusion, democracy, and social justice. Finally, I found that various factors and conditions are critical to the reported attainment of transformative outcomes, particularly in relation to the local program context, for example, reforms in local and international governments that support increased local control over resources and governance, organizational structures and priorities that are congruent with empowerment objectives, and previous experience with empowerment processes. I also highlighted deficiencies in the current empirical research and call on the evaluation community to improve research on transformative approaches to participatory evaluation by suggesting critical areas for practice and writing. These include strengthening research designs and the use of meta-evaluations, further defining and clarifying key terms, and providing rich detail to facilitate further learning in this area.
Keywords: participatory evaluation; transformative evaluation; empowerment